Can personality traits and intelligence compensate for background disadvantage? Predicting status attainment in adulthood. [article]. - Damian, Rodica I.; Su, Rong
This study investigated the interplay of family background and individual differences, such as personality traits and intelligence (measured in a large U.S. representative sample of high school students; N = 81,000) in predicting educational attainment, annual income, and occupational prestige 11 years later. Specifically, we tested whether individual differences followed 1 of 3 patterns in relati